The Implementation of Seven Efforts of Goat Farming At Sungai Nibung Village Gedung Meneng District Tulang Bawang Regency Lampung Province - Santika, Jaya; Tatik Inggriati, N W.; Suarta, G. (Jurnal Peternakan Tropika; Vol 7 No 2 (2019), 2019)
This research aims to find out social economy condition of goat farmer, implementation of seven efforts of goat farming, and finding out influential factors of the efforts. It was done at Sungai Nibung, Gedung Meneng district, Tulang Bawang regency, Lampung province within three months, November 2018 until January 2019. Both location and respondents were taken by purposive sampling. There were 36 goat farmers as respondents whose at least five goats and had farmed at least three years. To find out the correlations of the factors, Spearman correlative stage coefficient was used. The research showed the implementation of the efforts has not properly been promoted. Factors such as ages, formal education, farming experience, knowledge, and attitudes did not factually correlate to the efforts (p>0.05). Meanwhile, non-formal education had factual correlation (p<0.05). Keywords: implementation, seven efforts, goat farming